Regulatory Reform on Hydroelectric Power Plant Development in Indonesia - Naomi Helena Tambunan (Bappenas Working Papers, 2018)
This research essay will examine whether or not regulatory reform will succeed in providing a good regulation that gives significant effect to the development agenda, particularly in developing of the hydroelectric power plant which eventually fulfills citizen’s electricity needs. In order to obtain the license in developing hydroelectric power plant, the investor has to engage with at least 6 ministries at the national level and with the local government. The institutions are the Ministry of Public works, the Ministry of Energy and Mineral Resources, the Ministry of Forestry, Capital Investment Coordinating Board, State Electricity Company and Ministry of Finance. In each institution, the investors have to do some stages which mostly take a very long time. Until this recent time, the investors of hydroelectric power plant must comply with at least forty four national level regulations and should gain at least fourteen licenses from the various ministries. The figure does not include the license from the local government such as principle permits, location permits. Licenses zoning, building permits and nuisance permit (hinderordonnantie). Regulation problems that occurred in the process of developing hydroelectric power plant greatly hamper the effort on providing electricity to all Indonesia’s citizen. To overcome this issue, the national strategy on regulatory reform was made. While reconceptualization on regulatory making process strategy and the capacity building on the policy and regulatory maker strategy might increase the effectivity on the implementation of upcoming regulation, regulatory simplification is the effective strategy that can accurately overcome the existing regulatory problem in developing a hydroelectric power plant in Indonesia.